2017
DOI: 10.4103/ijpvm.ijpvm_229_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of melatonin and sertraline therapies on tinnitus: A randomized clinical trial

Abstract: Background:Tinnitus is the perception of noise or ringing without external acoustic stimulants which affects almost 10% of general population. Many therapies have been recommended including diet modifications, herbal remedies, and chemical drugs. Most common utilized drugs for tinnitus are melatonin and antidepressants such as sertraline which have been proven in different studies. In this study, we aimed to compare the efficacy of melatonin and sertraline in treating tinnitus for the first time.Methods:In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
4
0
5
Order By: Relevance
“…The sample size (61 patients) is in the range of that observed in previous studies on tinnitus (Morgenstern and Biermann 2002;Lopez-Gonzalez et al 2007;Tziridis et al 2014;Abtahi et al 2017) and higher than in several of them (Rosenberg et al 1998;Arda et al 2003;Cevette et al 2010;Radunz et al 2019). The high dropout rate (52.5%) noted in our study is worth mentioning, resulting in only 29 patients with complete data at the end of follow-up.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The sample size (61 patients) is in the range of that observed in previous studies on tinnitus (Morgenstern and Biermann 2002;Lopez-Gonzalez et al 2007;Tziridis et al 2014;Abtahi et al 2017) and higher than in several of them (Rosenberg et al 1998;Arda et al 2003;Cevette et al 2010;Radunz et al 2019). The high dropout rate (52.5%) noted in our study is worth mentioning, resulting in only 29 patients with complete data at the end of follow-up.…”
Section: Discussionmentioning
confidence: 44%
“…In assessing the effectiveness of this food supplement, we compared the tinnitus perception at baseline and after 3 months of treatment via the THI, an internationally validated and one of the most popular tinnitus instruments recommended in current guidelines (Cima et al 2019). Mean THI total score at baseline was 47.03, representing a moderate handicap (Zeng et al 2016), and being higher than that observed in earlier studies (Rosenberg et al 1998;An and Whitney 2015;Abtahi et al 2017). The 33.4% reduction in the total score was associated with a mild handicap at the end of follow-up (Zeng et al 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Research has been conducted on the tinnitus-inhibiting effects of tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) in the context of antidepressant use [ 25 - 32 ]. A Cochrane review published in 2012, which focused on four TCA studies and two SSRI studies, noted that both classes of antidepressants demonstrated that the evidence for or against their efficacy was not conclusive [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…O zumbido é a percepção de qualquer som na ausência de um estímulo acústico externo ( Lopez-Gonzales et al, 2007;Ferrari et al, 2014;Abtahi et al, 2017). É um sintoma decorrente de um distúrbio no organismo, e não uma doença (Lopez-Gonzales et al, 2007).…”
Section: Melatonina E Zumbidounclassified